Pengaruh Sosial Media Petshop terhadap Keputusan Pembelian - Lisha Adzanta Firmansyah (International Journal Administration, Business & Organization, 2022)
This research aims to investigate and analyze the impact of pet shop social media on purchasing decisions in the city of Bandung. The research methodology employed is quantitative descriptive, involving the collection of primary data through the distribution of questionnaires to 110 respondents. The analysis utilizes descriptive, correlation, and simple regression approaches. The research findings indicate that the use of social media significantly influences customers purchasing decisions at pet shops, with a significance value of 0.001. These results demonstrate that the utilization of social media has a strong and positive impact on purchasing decisions.